Heritage and Social Events as facilitators of Relationship Quality in wine sector - da Cunha, N. P.; Loureiro, S. M. C. (Proceedings of the International conference on Tourism and Ageing., 2016)
This study aims to explore how distributors and wine producers describe the organizational social capabilities they develop; as a facilitating facet of Relationship Quality (RQ). A total of eleven relationships are analysed based on 44 in-depth interviews. Findings reveals that Organisational Social Capabilities is a new RQ construct related with the organisational structure, the social behaviour and the history of the company.